Adverse Effects of Long-Term Oral Corticosteroids in the Department of Dermatology, Antananarivo, Madagascar - Sendrasoa FA; Ranaivo IM; Raherivelo AJ; Rapelanoro Rabenja F; Ramarozatovo LS (Dove Medical Press, 2021)
Fandresena Arilala Sendrasoa, Irina Mamisoa Ranaivo, Arifetraniaina Julia Raherivelo, Fahafahantsoa Rapelanoro Rabenja, Lala Soavina Ramarozatovo Department of Dermatology, Faculty of Medicine, University of Antananarivo, Antananarivo, MadagascarCorrespondence: Fandresena Arilala SendrasoaDepartment of Dermatology, Faculty of Medicine, University of Antananarivo, Antananarivo, MadagascarEmail nasendrefa@yahoo.frBackground: Long-term oral corticosteroids have an important role in dermatological care in Madagascar. However, significant adverse effects have been associated with continuous exposure to oral corticosteroids.Objective: We aim to assess the adverse effects of long-term corticosteroid therapy in patients seen in the Department of Dermatology at the University Hospital Joseph Raseta Befelatanana Antananarivo (UH/JRB), Madagascar, and to identify the risk factors associated with these adverse effects.Methods: A cross-sectional study was conducted during 4 months to assess the adverse effects of long-term corticosteroid therapy in patients seen in the Department of Dermatology. Patients treated with oral corticosteroids for more than 3 months were included in our study.Results: The prevalence of long-term use of oral corticosteroids in the Department of Dermatology of UH/JRB was 34.28%. A total of 51 patients were included and adverse effects occurred in 64.70% of this population. Repetitive infections and cutaneous adverse reactions were the most frequent adverse effects, in 23.52% and 11.76% of cases, respectively. There were no correlations between age, gender, type of disease treated, the molecule used or daily dose and the risk of adverse effects. Patients who received a corticosteroid dose of more than 40 mg daily (longer than 3 months) or a high cumulative dose of corticosteroids had a high risk of adverse effects.Conclusion: Repetitive infections and cutaneous adverse reactions are the most frequent adverse effects of long-term oral corticosteroid use. Prescribing the lowest effective dose may reduce the risk of these adverse effects. Furthermore, prevention of the adverse effects of corticosteroids through diet, calcium and vitamin D supplementation is strongly recommended during long-term oral corticosteroid therapy.Keywords: oral corticosteroids, repetitive infections, cutaneous adverse reactions, high dose